2010
DOI: 10.1007/s11920-010-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

DSM-5 Borderline Personality Disorder: At the Border Between a Dimensional and a Categorical View

Abstract: Recently, the DSM-5 Personality Disorders Workgroup offered its proposed revision for borderline personality disorder (BPD) and other personality disorder types ( http://www.dsm5.org ). According to the workgroup, this revision reflects an attempt to address excessive comorbidity among personality disorders, place personality pathology on continua, and replace individual behavioral criteria with personality traits. Essentially, the committee proposes a hybrid model of BPD (ie, categorical and dimensional)-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
3
45
0
1
Order By: Relevance
“…Results have been quite inconsistent, which may be due to differences in samples and measures of BPD used [18]. Moreover, correlations among the factors are typically very high, leading some authors to conclude that a more parsimonious one-factor model may fit the data best [1924]. Elaborating on this knowledge, it has been suggested that BPD may be most adequately described by a one-dimensional model, with factors representing varying degrees of severity on the underlying continuum [21, 24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have been quite inconsistent, which may be due to differences in samples and measures of BPD used [18]. Moreover, correlations among the factors are typically very high, leading some authors to conclude that a more parsimonious one-factor model may fit the data best [1924]. Elaborating on this knowledge, it has been suggested that BPD may be most adequately described by a one-dimensional model, with factors representing varying degrees of severity on the underlying continuum [21, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, correlations among the factors are typically very high, leading some authors to conclude that a more parsimonious one-factor model may fit the data best [1924]. Elaborating on this knowledge, it has been suggested that BPD may be most adequately described by a one-dimensional model, with factors representing varying degrees of severity on the underlying continuum [21, 24]. Taking into account the evidence demonstrating BPD to be a unidimensional construct, the additional value of investigating the differentiating multiple-factor structures has been noted to be more useful to understand BPD comorbidity and to plan treatment [25].…”
Section: Introductionmentioning
confidence: 99%
“…This disorder constitutes 10% of mental health clients observed in outpatient clinical settings and 15–20% of those in inpatient settings [4, 5]. BPD is a severe and complex psychological disorder characterized by pervasive instability in regulating emotions, self-image, interpersonal relationships, and impulse control [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous studies have shown that even mild borderline symptomatology in nonclinical populations is associated with significant impairment of functioning (e.g., Trull, Useda, Conforti, & Doan, 1997). Additionally, while controversies reign in the question of the utility of dimensional versus categorical (diagnostic) assessment of BPD and other personality disorders, a review of phenotypic and genetic studies generally supports the use of dimensional approaches (Trull, Distel, & Carpenter, 2011). Depression is highly comorbid with borderline personality disorder (Trull et al, 2010), and the present study controls for co-occurring depression at the time of BPD assessment.…”
mentioning
confidence: 99%